EVALUASI KESESUAIAN LAHAN BEKAS TANAMAN MARKISAH UNTUK BUDIDAYA TANAMAN TOMAT DI NAGARI SUNGAI NANAM KECAMATAN LEMBAH GUMANTI - LISWARTI, WITRA; Hermon, MP, Dr. Dedi; Juita, S.Pd., M.Si, Erna (Pendidikan Geografi, 2014)
ABSTRACT                   This study was purposed to know the suitability of  the land  for tomatoes on the trace land of marquisa at Nagari Sungai Nanam, Lembah Gumanti districts. The provided land  on the researched area 47 and the selected land was 5.This study used purposive sampling technique which used as intentionally. The data analysis was quantitative descriptive on the tables formed of the suitability land for tomatoes. It was viewed by texture, structure, elevation, depth effectiveness, pH and organic materialsThe results showed that: 1. The suitability trace land of marquisa for tomatoes viewed by texture at Nagari Sungai Nanam of Lembah Gumanti were found one category of suitable. 2. The suitability trace land of marquisa viewed by it sructure has two categories of suitable and almost suitable. 3. The suitability trace land of marquisa viewed by elwvation aspect has one category of suitable. 4. The suitability trace land of marquisa viewed by the depth effectiveness has two categories of almost suitable and not-suitable. 5. The suitability trace land of marquisa viewed by drainase has one category of suitable. 6. The suitability trace land property of marquisa viewed by pH has one category of suitable. 7. The suitability trace land of marquisa viewed by organics materials has two categoriesof less-suitable and suitable.